Evaluation of the feasibility and impacts of in situ simulation in emergency medicine—a mixed-method study protocol - Guillaume Martel; Marcel Émond; Jennifer Truchot; Valérie Boucher; Éliane Raymond-Dufresne; Christian Malo; Éric Brassard; Jean Marcotte; Geneviève Côté; Christian Garneau; Gino Bouchard (BMJ Open)
Introduction In situ simulation (ISS) consists of performing a simulation in the everyday working environment with the usual team members. The feasibility of ISS in emergency medicine is an important research question, because ISS offers the possibility for repetitive, regular simulation training consistent with specific local needs. However, ISS also raises the issue of safety, since it might negatively impact the care of other patients in the emergency department (ED). Our hypothesis is that ISS in an academic high-volume ED is feasible, safe and associated with benefits for both staff and patients.Methods A mixed-method, including a qualitative method for the assessment of feasibility and acceptability and a quantitative method for the assessment of patients’ safety and participants’ psychosocial risks, will be used in this study.Two distinct phases are planned in the ED of the CHU de Québec-Université Laval (Hôpital de l’Enfant-Jésus) between March 2021 and October 2021. Phase 1: an ISS programme will be implemented with selected ED professionals to assess its acceptability and safety and prove the validity of our educational concept. The number of cancelled sessions and the reasons for cancellation will be collected to establish feasibility criteria. Semistructured interviews will evaluate the acceptability of the intervention. We will compare unannounced and announced ISS. Phase 2: the impact of the ISS programme will be measured with validated questionnaires for the assessment of psychosocial risks, self-confidence and perceived stress among nonselected ED professionals, with comparison between those exposed to ISS and those that were not.Ethics and dissemination The CHU de Québec-Université Laval Research ethics board has approved this protocol (#2020–5000). Results will be presented to key professionals from our institution to improve patient safety. We also aim to publish our results in peer-reviewed journals and will submit abstracts to international conferences to disseminate our findings.